Early childhood constraint therapy for sensory/motor impairment in cerebral palsy: a randomised clinical trial protocol - Garey Noritz; Olena Chorna; Jill Heathcock; Alexandra Key; Helen Carey; Ellyn Hamm; Mary Ann Nelin; Micah Murray; Amy Needham; James C Slaughter; Nathalie L Maitre (BMJ Open)
Introduction Cerebral palsy (CP) is the most common physical disability in childhood. It is a disorder resulting from sensory and motor impairments due to perinatal brain injury, with lifetime consequences that range from poor adaptive and social function to communication and emotional disturbances. Infants with CP have a fundamental disadvantage in recovering motor function: they do not receive accurate sensory feedback from their movements, leading to developmental disregard. Constraint-induced movement therapy (CIMT) is one of the few effective neurorehabilitative strategies shown to improve upper extremity motor function in adults and older children with CP, potentially overcoming developmental disregard.Methods and analysis This study is a randomised controlled trial of children 12–24 months corrected age studying the effectiveness of CIMT combined with motor and sensory-motor interventions. The study population will comprise 72 children with CP and 144 typically developing children for a total of N=216 children. All children with CP, regardless of group allocation will continue with their standard of care occupational and physical therapy throughout the study. The research material collected will be in the form of data from high-density array event-related potential scan, standardised assessment scores and motion analysis scores.Ethics and dissemination The study protocol was approved by the Institutional Review Board. The findings of the trial will be disseminated through peer-reviewed journals and scientific conferences.Trial registration number NCT02567630.